Guidelines for Reporting of Figures and Tables for Clinical Research in Urology. (15th June 2020) - Vickers, Andrew J.; Assel, Melissa J.; Sjoberg, Daniel D.; Qin, Rui; Zhao, Zhiguo; Koyama, Tatsuki; Botchway, Albert; Wang, Xuemei; Huo, Dezheng; Kattan, Michael; Zabor, Emily C.; Harrell, Frank
Abstract: In an effort to improve the presentation of and information within tables and figures in clinical urology research, we propose a set of appropriate guidelines. We introduce six principles: (1) include graphs only if they improve the reader's ability to understand the study findings; (2) think through how a graph might best convey information, do not just select a graph from preselected options on statistical software; (3) do not use graphs to replace reporting key numbers in the text of a paper; (4) graphs should give an immediate visual impression of the data; (5) make it beautiful; and (6) make the labels and legend clear and complete. We present a list of quick "dos and don'ts" for both tables and figures. Investigators should feel free to break any of the guidelines if it would result in a beautiful figure or a clear table that communicates data effectively. That said, we believe that the quality of tables and figures in the medical literature would improve if these guidelines were to be followed. Patient Summary: A set of guidelines were developed for presenting figures and tables in urology research. The guidelines were developed by a broad group of statistical experts with special interest in urology.